Metronomic chemotherapy using oral cyclophosphamide and bevacizumab for recurrent cervical cancer: A multi-institutional retrospective study - Roze Isono-Taniguchi; Mayako Goto; Yumi Takimoto; Tomoko Ueda; Yu Wakimoto; Kayo Inoue; Kensuke Hori; Kimihiko Ito; Hiroshi Tsubamoto (Gynecologic Oncology Reports, 2022)
No standard chemotherapy is available after disease progression or anaphylaxis during platinum chemotherapy among patients with recurrent cervical cancer. Here we report the efficacy and toxicities of metronomic chemotherapy consisting of 50 mg of oral cyclophosphamide (CPA) daily and intravenous 15 mg/kg of bevacizumab (BEV) repeated every 3 weeks (CPA-BEV). Treated patients were retrospectively reviewed. Adverse events and response rates were recorded according to the Common Toxicity Criteria for Adverse Events (CTCAE) ver 5.0 and Response Evaluation Criteria In Solid Tumors ver 1.1, respectively. Eleven patients had been treated with CPA-BEV between 2016 and 2021.The pathologic types were squamous cell carcinoma in seven patients, adenocarcinoma in three, and large cell neuroendocrine carcinoma in one. Nine patients had primary concurrent chemoradiotherapy (CCRT). Five patients received more than one prior chemotherapy (excluding CCRT). Six patients had progressive disease during prior platinum-based chemotherapy, four patients recurred within 6 months of the last platinum administration, and one patient had platinum anaphylaxis. Grade 3 or more hematologic toxicities and grade 2 or more non-hematological toxicities were observed in one with grade 3 neutropenia and in one with grade 2 proteinuria, respectively. The median duration of chemotherapy was 2.8 months (range 0.2–30.6 months). One patient had CR but none had PR. Median progression-free survival was 2.8 months (95 %CI: 2.1–10.7 months), and median overall survival was 13.6 months (95 %CI: 8.4–33.7 months). In conclusion, the CPA-BEV regimen showed favorable antitumor activity with minimal toxicity and is promising candidate for second-line chemotherapy.